Effect of Seed Grading by Size on Germination and Growth of Pine Seedlings - Ghosh, R. C.; Singh, Bakhshish; Sharma, K. K. (Indian Forester, 1976)
A nursery study on Pinus roxburghii, P. caribaea, and P. oocarpa was conducted in the research nursery of the Forest Research Institute, Dehra Dun (India) to find the effect of seed grading (by size) on germination and growth of pine seedlings. The results show that medium sized seed gave significantly higher mean total germination percent and plant percent as compared to the large or small sized seeds. Moreover, medium sized seed gave higher mean daily germination, peak value (of germination), germiuation value, total biomass, height growth and root/shoot ratio of the seedlings as compared to the other two grades. Small sized seed gave significantly higher germination percent and germination value as compared to the large sized seed but the seedlings raised from large, sized seed had higher total biomass than the seedlings raised from the small seed. Seedlings of Pinus roxburghii had the highest Root/Shoot ratio and total biomass, followed by P. oocarpa and P. caribaea.